Analisis Kemenangan Pasangan Khairul Anwar dan Agus Widayat pada Pemilukada Dumai 2010 - ADLIN ADLIN (Universitas Sumatera Utara, 2014)
In the history of general election of regional head (Pemilukada) at Dumai City (Kota Dumai), the incumbent candidate always beaten by new challenger candidate. Interestingly, Khairul Anwar-Agus Widayat is the winner of the general election of regional head 2010. They are candidates in the election Dumai in 2005 and has been a crushing defeat compared to Zul AS-Sunaryo. This study explains why they succeed win that general election. This study is using po-litical behavior approach. Collecting data of this study is using field research and data analysis using quantitative and qualitative method. The finding is,there are three main causes of victory Khairul Anwar-Agus Widayat. First, this candidates promising change issues. Second, there are many people were disappointed to the icumbent. Third, there are correspondence between vision with the will of the people. Voter has made his choice based on many factors, and other factors have a smaller effect than the three factors.Keywords: Incumbent, challenger, local election.